Influências e recursos extrafamiliares na construção da coparentalidade: um estudo qualitativo - Maria do Carmo Zuzarte Cortezão de Magalhães Ramalho (2021)
The birth of the first child leads to new roles in life, new tasks and implies the reorganization of intra- and inter-family relationships, incorporating a challenging and demanding phase for new parents. The construction of coparenting begins during the pregnancy period and involves a new developmental task during a transition to parenthood, which is relevant to an adapted transition. The influences and resources available in the couple's context influence the construction of coparenting, playing a protective role in the transition. Regarding the period of pregnancy, few studies investigate (1) the expanding trajectory of coparenting, (2) the support perceived and received by new parents and (3) how couples anticipate that coparenting is shaped on a extrafamilial level by influences and available resources. Using a qualitative methodology, this study seeks to analyze the identification of the components of coparenting by couples, the influences and resources identified and what is their role in the construction of coparenting. The sample was found by 10 heterosexual couples (N = 20) in the third trimester of pregnancy of their first child. Semi-structured interviews were managed individually through an online platform. The data showed two themes: In the first theme, perspectives on coparenting, four sub-themes related to the dimensions of coparenting presented by the participants were identified. In the second theme, external influences and resources, six resources and sources of support for parenting emerged. Integrated in the portuguese context, the dimensions of coparenting and the support resources identified by the couples are guided and discussed, highlighting their relationship.